Biocontrol potential of endophytic Bacillus subtilis A9 against rot disease of Morchella esculenta - Chen, Xue; Zhang, Yin; Chao, ShengQian; Song, LiLi; Wu, GuoGan; Sun, Yu; Chen, YiFan; Lv, BeiBei (Frontiers in Microbiology, 2024)
Introduction: Morchella esculenta is a popular edible fungus with high economic and nutritional value. However, the rot disease caused by Lecanicillium aphanocladii, pose a serious threat to the quality and yield of M. esculenta. Biological control is one of the effective ways to control fungal diseases.In this study, an effective endophytic B.subtilis A9 for the control of M. esculenta rot disease was screened, and its biocontrol mechanism was studied by transcriptome analysis. In total, 122 strains of endophytic bacteria from M. esculenta, of which the antagonistic effect of Bacillus subtilis A9 on L. aphanocladii G1 reached 72.2% in vitro tests. Biological characteristics and genomic features of B. subtilis A9 were analyzed, and key antibiotic gene clusters were detected. Scanning electron microscope (SEM) observation showed that B. subtilis A9 affected the mycelium and spores of L. aphanocladii G1. In field experiments, the biological control effect of B. subtilis A9 reached to 62.5%. Furthermore, the transcritome profiling provides evidence of B.subtilis A9 bicontrol at the molecular level. A total of 1246 differentially expressed genes (DEGs) were identified between the treatment and control group. Gene Ontology (GO) enrichment analysis showed that a large number of DEGs were related to antioxidant activity related. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that the main pathways were Nitrogen metabolism, Pentose Phosphate Pathway (PPP) and Mitogen-Activated Protein Kinases (MAPK) signal pathway. Among them, some important genes such as carbonic anhydrase CA (H6S33_007248) ,catalase CAT (H6S33_001409), tRNA dihydrouridine synthase DusB (H6S33_001297) and NAD(P)-binding protein NAD(P)BP (H6S33_000823) were found. Furthermore, B. subtilis A9 considerably enhanced the M. esculenta activity of Polyphenol oxidase (POD), Superoxide dismutase (SOD), Phenylal anineammonia lyase (PAL) and Catalase (CAT).This study presents the innovative utilization of B. subtilis A9, for effectively controlling M. esculenta rot disease. This will lay a foundation for biological control in Morchella, which may lead to the improvement of new biocontrol agents for production.